Megalencephaly-Capillary Malformation Syndrome: a Case Series with Expansion of Phenotype - Cordisco, M.R.; Baselga, E.; Ako-Adjei, D.; Persico, S.; Lanoel, A.; Greco, M.F.; Maccario, M.F.; Mirzaa, G.M.; Fernandez Faith, E. (European Journal of Pediatric Dermatology, 2026)
Background/Objectives: Megalencephaly-capillary malformation polymicrogyria syndrome (MCAP) is a rare genetic disorder characterized by megalencephaly, capillary malformation and somatic overgrowth, caused by somatic variants in PIK3CA. We report a case series of 12 patients with MCAP with a focus on clinical manifestations. Methods: Retrospective case series at tertiary referral centers. Results: 12 patients with MCAP syndrome were identified. All patients presented with reticulated capillary malformations, 50% had a combination of reticulated and confluent capillary malformations. A fronto-facial capillary malformation was present in a majority of patients (83%), with lumbosacral involvement in 42%. Two patients developed a benign, non-specific vascular tumor on the trunk. Digital anomalies, somatic overgrowth and neurologic manifestations of variable severity were present in all patients. Conclusions: Clinical overlap exists between MCAP and other PIK3CA-related overgrowth spectrum disorders. Cutaneous manifestations are salient features of MCAP, their recognition is critical for an early diagnosis.